Wideband electromagnetic interference filtering power divider with a wide stopband using the genetic algorithm - Dai, Zhou; Li, Wei; Ma, Chenxin; Zhang, Wenfei; Tang, Wanchun (Frontiers in Physics, 2023)
This paper proposes a new design of an electromagnetic interference wideband filtering power divider (FPD) with a wide stopband based on the genetic algorithm (GA). A set of data structures is constructed by describing the corresponding connection method between the basic units and their electrical parameters in the three-port design. Then, the GA is used to find the appropriate design topology and electrical parameters, including isolation resistances, to meet FPD specifications by optimizing the data structures. For validation, one prototype is implemented. The results indicate that the new wideband FPD exhibits compact size, sharp roll-off, and good in-band isolations.